The Adaptive Capacity of Corals Based on the Health Level to Estimate the Carrying Capacity of the Marine Ecotourism in Enggano Island - Yar Johan; Fredinan Yulianda; Rahmat Kurnia; Ismudi Muchsin (Journal Omni-Akuatika, 2018)
Enggano Island is one of the outermost islands of Indonesia. Among the recoverable resources that exist in Enggano Island are coral reef ecosystems. A coral reef ecosystem is also one of the ecosystems with a high level of biodiversity productivity having a major role as habitats, feeding places, and the coastal protection from the crashing of waves and strong currents. Currently, coral reefs are being destroyed either by nature or humans. The ability of an ecosystem to adapt to a disturbance or potential damage is called adaptive capacity. The aim of the study was to assess the adaptive capacity of corals in terms of their health levels to estimate the carrying capacity of marine ecotourism. The observation method used was survey method. Adaptive capacity measurements were carried out by analyzing six parameters: hard coral cover (%), distances from human settlements (km), dominance of lifeform, types of lifeform, reef fish species, and coral reef depth (m). The results of this study showed that Enggano Island corals had the adaptive capacity that fell into two categories: medium and adaptiveEnggano Island is one of the outermost islands of Indonesia. Among the recoverable resources that exist in Enggano Island are coral reef ecosystems. A coral reef ecosystem is also one of the ecosystems with a high level of biodiversity productivity having a major role as habitats, feeding places, and the coastal protection from the crashing of waves and strong currents. Currently, coral reefs are being destroyed either by nature or humans. The ability of an ecosystem to adapt to a disturbance or potential damage is called adaptive capacity. The aim of the study was to assess the adaptive capacity of corals in terms of their health levels to estimate the carrying capacity of marine ecotourism. The observation method used was survey method. Adaptive capacity measurements were carried out by analyzing six parameters: hard coral cover (%), distances from human settlements (km), dominance of lifeform, types of lifeform, reef fish species, and coral reef depth (m). The results of this study showed that Enggano Island corals had the adaptive capacity that fell into two categories: medium and adaptive